Changes in demand: the roles of academic leaders in Malaysia - Mansor, Zuraina; Han, Chun Kwong (ERM Publications, 2013)
Education stands as an important investment in building human capital, who will become a driver for innovation and economic growth in the world-wide market. It is only through improving the educational status of a society that the multi-faceted development of its people can be achieved and prolonged. The main objective of this study is to discuss the transformational process of academic leaders’ roles and responsibilities due to the impacts and implications of the globalization and internationalization of Malaysian higher educational institutions (HEIs). The paper is focused on the roles and responsibilities of academic leaders within the HEIs based on research conducted with academic leaders from public and private universities. The respondents were asked about their strategic objectives and their responsibilities in supporting the globalisation objectives and how they cope with the dynamic environmental challenges from within or outside their organizations.